Step
*
1
of Lemma
rpolynomial-locally-non-zero
1. n : ℕ
2. a : ℕn + 1 ⟶ ℝ
3. (Σi≤n. a_i * r0^i) < r0
4. r0 < (Σi≤n. a_i * r1^i)
5. u : ℝ
6. v : ℝ
7. r0 ≤ u
8. u < v
9. v ≤ r1
⊢ ∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ λx.(Σi≤n. a_i * x^i)(z) ≠ r0)
BY
{ Assert ⌜ℕ+⌝⋅ }
1
.....assertion..... 
1. n : ℕ
2. a : ℕn + 1 ⟶ ℝ
3. (Σi≤n. a_i * r0^i) < r0
4. r0 < (Σi≤n. a_i * r1^i)
5. u : ℝ
6. v : ℝ
7. r0 ≤ u
8. u < v
9. v ≤ r1
⊢ ℕ+
2
1. n : ℕ
2. a : ℕn + 1 ⟶ ℝ
3. (Σi≤n. a_i * r0^i) < r0
4. r0 < (Σi≤n. a_i * r1^i)
5. u : ℝ
6. v : ℝ
7. r0 ≤ u
8. u < v
9. v ≤ r1
10. ℕ+
⊢ ∃z:ℝ. ((u ≤ z) ∧ (z ≤ v) ∧ λx.(Σi≤n. a_i * x^i)(z) ≠ r0)
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  a  :  \mBbbN{}n  +  1  {}\mrightarrow{}  \mBbbR{}
3.  (\mSigma{}i\mleq{}n.  a\_i  *  r0\^{}i)  <  r0
4.  r0  <  (\mSigma{}i\mleq{}n.  a\_i  *  r1\^{}i)
5.  u  :  \mBbbR{}
6.  v  :  \mBbbR{}
7.  r0  \mleq{}  u
8.  u  <  v
9.  v  \mleq{}  r1
\mvdash{}  \mexists{}z:\mBbbR{}.  ((u  \mleq{}  z)  \mwedge{}  (z  \mleq{}  v)  \mwedge{}  \mlambda{}x.(\mSigma{}i\mleq{}n.  a\_i  *  x\^{}i)(z)  \mneq{}  r0)
By
Latex:
Assert  \mkleeneopen{}\mBbbN{}\msupplus{}\mkleeneclose{}\mcdot{}
Home
Index